Mengintegrasikan Eco Print dan Eco Enzim: Produk Ramah Lingkungan Multi Fungsi di Kampung Delik Sari, Semarang - Honorata Ratnawati Dwi P; Susintowati; Janti Sugiyastuti; Suparmi (Universitas 17 Agustus 1945 Semarang, 2023)
The textile and agriculture industries are sectors that have a large impact on the environment. Chemicals used in the printing and dyeing processes of cloth and in fertilization can contaminate water and soil, and affect human health. Therefore, the emergence of eco print technology and eco enzymes is an attractive alternative to reduce this negative impact. This community service aims to study the potential use of eco print and eco enzymes in producing multi-functional environmentally friendly products in Delik Sari Village, Semarang. The research method used is training by presenting resource persons in accordance with the fields: eco print and eco enzymes Meanwhile, making eco prints aims to increase better product results and more diverse product diversification. Eco-enzymes produced by bacteria and fungi are used as basic ingredients for making environmentally friendly soaps and household cleaners. The results of community service show that the use of eco print and eco enzyme technology can produce quality fabric products with attractive and durable colors. In addition, the waste products from the eco print and eco enzyme processes can be used as organic fertilizer which is useful for agriculture in Delik Sari Village. Thus, eco print and eco enzyme technologies have great potential to produce multi-functional environmentally friendly products that can improve the welfare of the people of Kampung Delik Sari, Gunung Pati sub-district, Semarang City.